Heterotic capability of five crosses for quantitative traits in bread wheat (Triticum aestivum L.) with inbreeding depression studies using generation mean analysis - Busa, Darshika; Pansuriya, Ashwin; Vekaria, Deep; Singh, Chandrakant; Kulkarni, G U; Patel, Jagdish (Journal of Cereal Research, 2025)
Six generations, namely P1, P2, F1, F2, BC1 and BC2 of five crosses of bread wheat viz., AKAW 4842 x Raj 4238, AKAW 4924 x RW 5, DBW 39 x MP 3353, GW 11 x DWAP 1540 and GW 455 x UP 2968 were developed to estimate the extent of heterosis and inbreeding depression and underlying genetic causes for different characters in bread wheat. The analysis of variance between families (crosses) revealed that the mean square due to crosses were highly significant for all the characters. The analysis of variance among progenies (generations) within each family (cross) indicated significant differences among six basic generation means for all the characters studied in all the five crosses. In the present study all the crosses depicted significant and positive mid parent heterosis and heterobeltiosis for grain yield per plant and almost all the component traits. Among which crosses AKAW 4842 x Raj 4238, AKAW 4924 x RW 5, GW 11 x DWAP 1540 and GW 455 x UP 2968 depicted negative inbreeding as well as significant and positive mid parent heterosis and heterobeltiosis for grain yield per plant therefore, intermating in F2 generation may be advantageous for improving particular character for above mentioned crosses. Generally, the character like grain yield per plant governed by fixable additive gene effect can be improved through pedigree selection method.